Penerapan Teknik Rumpang dalam Pembelajaran Demokrasi: Membangun Pola Pikir Demokratis Siswa Fase B Sekolah Dasar berdasarkan Teori Konstruktivisme Sosial - Ratna Fitria; Warlim; Aang Supriatna; Vini Agustiani H (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the cloze technique in democratic learning to foster democratic mindsets among Phase B elementary school students (grades 3-4) grounded in Vygotsky's social constructivism theory. The research employed Classroom Action Research (CAR) with two cycles involving 25 third-grade students at SDN Kabupaten Bandung Barat. Data collection utilized democratic attitude observation sheets, teacher activity observation sheets, and field notes. The findings revealed a significant progressive improvement in students' democratic dispositions, with mean scores increasing from 41.2 (pre-cycle) to 65.8 (cycle I), reaching 82.4 (cycle II), with 88% of students achieving the "good" category. The cloze technique successfully facilitated students' active engagement in meaning-making processes through scaffolded discourse completion activities, promoting critical thinking, deliberation skills, and respect for diverse perspectives. This research contributes to the theoretical development of democratic pedagogy in elementary education and offers practical implications for integrating constructivist approaches in citizenship education, demonstrating that structured linguistic gaps in democratic-themed texts can serve as effective cognitive tools for constructing democratic understanding. The findings suggest that the cloze technique, when embedded within a social constructivist framework, provides a viable pedagogical strategy for cultivating democratic citizenship competencies in early childhood education.